Matrix metalloproteinases as profibrotic factors in terminal ileum in Crohn's disease. - Warnaar, N; Hofker, H; Maathuis, M; Niesing, J; Bruggink, A; Dijkstra, G; Ploeg, R; Schuurs, T (2006)
BACKGROUND: Returning stenosis in Crohn's disease (CD) patients is poorly understood. After resection, newly developed strictures are seen within 10 years in 50% to 70%. Matrix metalloproteinases (MMPs) are involved in matrix-turnover processes. This study analyzes spatial expression of MMP-1, MMP-3, MMP-9, tissue inhibitor of MMP-1, and collagen III to get better insight in tissue remodeling of terminal ileum of CD patients. METHODS: Expressions were analyzed on mRNA and the protein level (MMP-1, MMP-3) in segments from resected terminal ileum from CD and control patients. In CD, macroscopic distinction was made between proximal resection margin, prestenotic, and stenotic tissue. Immunohistochemistry allowed for expression analyses transmurally. RESULTS: MMP-1 and MMP-3 gene expression was up-regulated (P < 0.05) in both prestenotic and stenotic tissue. MMP-1 protein was significantly up-regulated in submucosal and muscular tissue of prestenotic parts and in muscular tissue of stenotic Crohn samples. MMP-3 protein was significantly up-regulated in all layers of prestenotic and stenotic Crohn samples. Even in submucosa of proximal resection margin tissue, MMP-3 expression was significantly higher than in controls. CONCLUSION: Surprisingly, in proximal resection margin tissue up-regulated MMP-3 was seen. This suggests that in nonresected terminal ileum, in which anastomosis is made, tissue turnover is present, which may account for the high recurrence of intestinal strictures.